Вплив сучасних ЗМІ на формування історичної пам’яті українців та поляків - Dobrzhanskiy, Oleksander (Донецький національний університет імені Василя Стуса, 2018)
Mass media is a powerful means of influence on the formation of the social stereotypes and historical memory in the society. The way the information is presented and the key points are highlighted directly depends on the awareness of the society and formation of the historical memory of the people. Modern social discourse between Ukraine and Republic of Poland on the issue of the historical past namely of the events connected with the opposition between Ukrainians and Poles on the territory of Volyn during the years the Second World war negatively influences on the historical memory.
Keywords: historical memory; international conflicts; social and historical stereotypes; Ukraine; Republic of Poland; mass media